KEPUASAN AKSEPTOR PADA PELAYANAN MOPVASEKTOMI DI SATYA GATRA KOTA SURABAYA - VIDAYATI, LELLY APRILIA (NHM PRESS, 2024)
Among the various family planning services available, vasectomy is still rarely popular with the general public. The purpose of the study was to identify the satisfaction of Vasectomy acceptors at Satya Gatra Surabaya City. The research used a quantitative descriptive design. There are nine variables raised, which are the requirements, mechanism, completion time, cost/tariff, service specifications, competence of implementers, behavior of implementers, handling of service complaints, and facilities and infrastructure. Population, sample and research time, namely all MOP acceptors at Satya Gatra Surabaya City with a total sampling of 35 people in July-August 2024. Data collection methods using a questionnaire and measured by a Likert scale. Data analysis used descriptive analysis with frequency distribution. The results of the study concluded that in the first variable, the answer was satisfied, the 2nd variable was satisfied, the 3rd variable was satisfied, the 4th variable was very satisfied, the 5th variable was very satisfied, the 6th variable was very satisfied, the 7th variable was very satisfied, the 8th variable was satisfied, the 9th variable was satisfied. Although the overall value of the indicator is categorized as satisfied, there are those who have less satisfied answers, namely system indicators, mechanisms, procedures and infrastructure indicators.